Adapted Physical Education in Self-Contained Settings: Planning for Successful Instruction. (2nd September 2016) - Wilson, Wesley J.; Beamer, Jennifer; Block, Martin E.
Abstract : Nearly 30% of U.S. schools have students with severe disabilities who participate in a self-contained adapted physical education (SAPE) setting, separate from their typically developing classmates. It is imperative that physical education teachers become familiar with pedagogical strategies for planning and teaching SAPE. The purpose of this article is to offer several pedagogical strategies and to provide a detailed sample lesson plan with assessment, goals and a diagram of the setup for students in a SAPE setting.